Pengembangan Bahan Ajar Menulis Cerita Pendek dengan Media Adobe Flash - Siti Subaidah; Susilo Susilo; Mohammad Siddik (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
This development aims to develop teaching materials for writing short stories with adobe flash SMP Class IX. The scope of this development is limited only to planning, material and evaluation in the learning process. The method used in this research is Research and Development (R&D), using a development research design using the Brog & Gall model. Teaching material development results obtained material expert test results 82% were declared feasible, media expert test 86% were declared feasible, small group field test 80% declared good, a large group field test 82.3% was declared good. So overall the data obtained from the development of instructional materials with adobe flash media is declared feasible, teaching materials with adobe flash media are effective in increasing motivation, focus and responsiveness while the evaluation results provide increased student ability in writing short stories.